A 21-Years-Old Man with Mesial Temporal Lobe Epilepsy and Dystonia: A Rare Case Report - Puspita Sari Sugiyarto Putri; Diah Kurnia Mirawati; Ervina Arta Jayanti Hutabarat (Department of Neurology Faculty of Medicine Universitas Sebelas Maret, 2024)
Background: Mesial temporal lobe epilepsy (MTLE) with dystonia is a rare case. Seizures and movement disorders have almost the same phenomenology, so it is often difficult to distinguish them. In this study, we report a unique case of MTLE and co-occurring dystonia. Case: A 21 years old male with complaints of seizures since 4 years ago. Seizures of one body jerking and drooling with a duration of less than 5 minutes. Prior to the seizure the patient was nauseous then vomited and followed by an empty mind, after the seizure the patient was confused. The patient also complained of unconscious movements in his right hand since 8 years ago. The movements disappeared when the patient slept. Physical examination revealed dystonic movement with a sensory trick on the right hand. Magnetic resonance imaging (MRI) of the brain with contrast showed bilateral hippocampal atrophy accompanied by left hippocampal sclerosis. Blood laboratory results, electroencephalography, and neurobehavior examination were within normal limits.. Discussion: MTLE can be caused by mutations in SCN1A, VPS13A, C90RF72, or TDP 43. Dystonia can be caused by mutations in SCN1A, TUBB4A, TOR1A, THAP1, or GNAL. SCN1A causes an increase in sodium influx, causing depolarization which causes clinical manifestations in the form of seizures and dystonia. For some disorders, although genetic causes have been identified, the molecular pathophysiology remains largely unknown, requiring further research. Conclusion: For some disorders, although genetic causes have been identified, the molecular pathophysiology remains largely unknown, requiring further research.